Fatores relevantes ao processo de cria????o do conhecimento associado ?? inova????o em empresa de base tecnol??gica - Fran??a, Antonio de Sant'Anna Limongi (2013)
The present essay aims at understanding how the process of knowledge creation, associated with innovation in technology-based companies, happens. From a theoretical standpoint, our objective is to understand the process through the analysis of factors that are relevant to the process itself. Based on several theories on the study of innovation and on acquisition and sharing of knowledge, the survey examined five innovation cases at Siemens, after research was done in the strategic level of the company. The field research, focused on each one of the studied cases, with contexts, participants, variables and specific phenomena, was based on the multiple-case study methodology, considering the theories of Yin and Eisenhardt, mainly. From the studied theories, two questionnaires were designed: the first having in mind the strategic perspective, and a second one focusing on the operational perspective of innovative processes. From these two perspectives and after a survey and data analysis phase, a construct was created, which introduced the theoretical dimensions of the research. The first perspective created an analysis dimension Dimension 01, which characterizes the strategic profile of the company. The second perspective created eight dimensions of operational analysis: Dimension 02 Kinds of Innovation; Dimension 03 Initial Idea; Dimension 04 Development; Dimension 05 Investment and Protection; Dimension 06 Predictable / Unimaginable Problems; Dimension 07 Users Knowledge; Dimension 08 Solution Integration; Dimension 09 Individuals and Paradigms. The definition of each of the dimensions was the result of the categorization of questions and answers that had the same theoretical nature. The results of the research, vis-a-vis the theories used, led to the general objective, which indicates the relevant factors in knowledge creation associated with innovation in technology-based companies. The understanding that results from the analysis of this essay can contribute to improve methods of management and development, typical of the innovative process in companies, which is, by its own nature, dynamic and complex.